2000
DOI: 10.1093/glycob/10.9.865
|View full text |Cite
|
Sign up to set email alerts
|

The changes in glycosylation after partial hepatectomy enhance collagen binding of vitronectin in plasma

Abstract: Vitronectin is a multifunctional glycoprotein present in the extracellular matrix and plasma. Changes in rat vitronectin were studied during liver regeneration after partial hepatectomy. Carbohydrate concentrations of vitronectin decreased to 2/3 of sham-operated rats at 24 h after partial hepatectomy. Carbohydrate composition and lectin reactivity indicated that N-glycosylation and sialylation of vitronectin changed markedly after partial hepatectomy, while amino acid composition did not change significantly.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
32
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 40 publications
3
32
0
Order By: Relevance
“…This is similar to previous data showing that glycosylation significantly alters the pI of other similar glycoproteins (20,21). Moreover, glycosylation can provide conformational and structural stability (22,23) and may facilitate correct folding (23,24) and importantly modulate ligand binding and functions (20,25,26). We found that rLILRA3 in its non-glycosylated form required extensive refolding steps, was highly susceptible to aggregation/oxidation, and was non-functional despite being of high purity and high yield (up to 15 mg/liter).…”
Section: Discussionsupporting
confidence: 90%
“…This is similar to previous data showing that glycosylation significantly alters the pI of other similar glycoproteins (20,21). Moreover, glycosylation can provide conformational and structural stability (22,23) and may facilitate correct folding (23,24) and importantly modulate ligand binding and functions (20,25,26). We found that rLILRA3 in its non-glycosylated form required extensive refolding steps, was highly susceptible to aggregation/oxidation, and was non-functional despite being of high purity and high yield (up to 15 mg/liter).…”
Section: Discussionsupporting
confidence: 90%
“…Further study demonstrated that multimerization of rat VN increases during liver regeneration after partial hepatectomy and that increases in the collagen-binding activity are synchronized with the glycan changes in vivo (15). The molecular mass of VN purified from partially hepatectomized (PH-VN) rats at 24 h had shrunk to 65 kDa compared with the 68 -69 kDa of VNs from sham-operated (SH) and non-operated (NO) rats.…”
mentioning
confidence: 99%
“…2B, the purified vitronectins bound to type I collagen by ELISA in a concentration-dependent manner, and PH-VN was found to exhibit much greater binding to collagen, about 3 times higher than that of SH-VN and NO-VN (Uchibori-Iwaki, H., et al 2000). The enhanced binding of PH-VN to immobilized collagen shown by ELISA was supported by surface plasmon resonance (SPR), as shown in Fig.…”
Section: Changes In Collagen-binding Activity Of Plasma Vitronectin Dmentioning
confidence: 73%
“…1977) of PH-VN was 0.040 when taking that of SH-VN as 0.0. All three vitronectins had the same N-terminal sequence, indicating that the three vitronectins had high homology among the primary sequence (Uchibori-Iwaki, H., et al 2000).…”
Section: Changes In Collagen-binding Activity Of Plasma Vitronectin Dmentioning
confidence: 99%
See 1 more Smart Citation